The Impact of Antenatal and Postnatal Factors on the Development of the Pulmonary Microvasculature in Preterm Infants - Raluca Chirculescu; Ruxandra Viorica Stănculescu; Paul Cristian Bălănescu; Gheorghe Peltecu (Children)
This research aimed to assess the influence of prenatal and postnatal factors on the remodeling of the pulmonary microvasculature. Methods: The investigation analyzed 67 cases of preterm infants, whose lifespans ranged from 1 day to 149 days. After selecting the cases from the autopsy database, two lung tissue microarrays were created. Histological slides were stained using the hematoxylin and eosin technique to precisely capture the microscopic details. For the assessment of pulmonary microvascularization and the media layer of the vascular walls, an immunohistochemical analysis was performed utilizing CD34 and SMA markers. Results: Following the assessment of the quantity of capillaries positive for CD34, a negative correlation was identified between the average capillary count per alveolus and the duration of oxygen therapy. Preterm infants who developed pulmonary fibrosis exhibited an average reduction of 5.43 capillaries in comparison to other newborns. Preterm neonates born to mothers with preeclampsia exhibited an average reduction of 2.82 capillaries compared to those born to mothers unaffected by this pregnancy complication. A positive correlation was evident between increased thickness of the arteriolar media, lifespan, and the duration of oxygen therapy, as well as in those preterm infants who developed pulmonary fibrosis. Conclusions: Antenatal risk factors did not exert a significant impact on pulmonary vascular remodeling, whereas postnatal influences, particularly oxygen therapy, demonstrated a detrimental effect on the density of capillary structures within the alveolocapillary membrane. Premature neonates with increased thickness of the arteriolar media had a greater susceptibility to pulmonary hypertension.